Preparation of a Thermally Sensitive Ammonium Perchlorate - Oommen, C. (2014)
Proceedings of the 2003 International Autumn Seminar on Propellants, Explosives and Pyrotechnics (2003 IASPEP) - Theory and Practice of Energetic Materials